COMMUNITY PREFERENCES FOR PRIVATE ISLAMIC EDUCATION IN MASOHI CENTRAL MALUKU - Sawal, Sawal; Latif Saifi, Imran (Conciencia, 2025)
This study aims to analyse community preferences regarding private Islamic education in Masohi City, Central Maluku, in the post-conflict socio-religious context. The study uses a mixed-methods approach, combining qualitative and quantitative methods. Qualitative data were obtained through in-depth interviews, observations, and documentation involving school principals, teachers, parents of students, and community leaders, and analysed using Miles and Huberman's interactive model. Quantitative data were collected through a survey using proportional stratified sampling techniques representing 10% of students in each school, namely SD Islam Al-Bina (29 respondents), MIT Nurul Falah (30 respondents), and SD Muhammadiyah Masohi (18 respondents), with a total of 77 respondents and a margin of error of approximately 11–12% at a 95% confidence level. The results showed that community preferences were influenced by five main factors, namely (1) religious motivation, (2) quality of education, (3) school facilities and services, (4) socio-cultural dimensions, and (5) economic factors and accessibility. These findings also reveal the transformation of the role of private Islamic schools as a substitute for Islamic boarding schools in character building, strengthening religious identity, and social reconstruction of post-conflict communities. This study contributes theoretically to the development of Islamic education sociology studies and practically provides an empirical basis for strengthening private Islamic education policies and institutions in Eastern Indonesia.